Clinical Remission and Low Disease Activity Outcomes Over 10 Years in Systemic Lupus Erythematosus. Issue 6 (10th May 2019) - Tselios, Konstantinos; Gladman, Dafna D.; Touma, Zahi; Su, Jiandong; Anderson, Nicole; Urowitz, Murray B.
Abstract : Objective: A recent study conducted by our clinical group demonstrated that low disease activity (LDA), defined as a clinical Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI‐2K) score ≤2, maintained for 12 months, confers the same risk for damage accrual as complete remission after 2 years. The aim of the present study was to assess the validity of these findings in the long term (10 years). Methods: Patients in the inception cohort of the Toronto Lupus Clinic, who had a minimum follow‐up of 10 years and no interval >18 months between consecutive visits, were included in the analysis. Prolonged clinical remission was defined based on a SLEDAI‐2K score of 0 (serology excluded), achieved within the first 5 years of enrollment and maintained for ≥10 years. Prolonged LDA was defined as SLEDAI‐2K score ≤2 (serology excluded) with the same time frame restrictions. Results: Of 267 patients, 27 (10.1%) achieved prolonged clinical remission and 48 (18%) attained prolonged LDA. There were no differences regarding demographic, clinical, and immunologic variables at any time. The mean prednisone dose at enrollment was higher in patients in whom remission was achieved, while patients with prolonged LDA were taking antimalarials more frequently, both at enrollment and after the 10‐year time period. Cumulative damage and flare rate after 10 years, and mortality throughout follow‐up were comparable. SLE in patients in the prolonged LDA group was in complete remission for 76% of the follow‐up time. Conclusion: Prolonged clinical remission and LDA were demonstrated in 10.1% and 18% of our patients, respectively, and comparable outcomes were demonstrated in the long term, rendering sustained LDA an acceptable treat‐to‐target outcome in SLE.